PegIFN-α2a for the treatment of chronic hepatitis B and C: a 10-year history - Degasperi, Elisabetta; Viganò, Mauro; Aghemo, Alessio; Lampertico, Pietro; Colombo, Massimo (Expert review of anti-infective therapy, 2013)
Chronic HBV and HCV are progressive diseases leading to cirrhosis and liver transplantation. Persistent viral eradication or suppression can positively affect the natural course of the infection, by preventing disease progression. Since its introduction more than 30 years ago, IFN-α has represented the foundation of HBV and, lately, anti-HCV treatment. Pegylation of the IFN-α molecule (PegIFN-α2a) has provided improvements in both efficacy and administration schedule, thus becoming part of the standard-of-care regimen for HCV and HBV therapy in the last 10 years. Currently, treatment of finite duration with PegIFN-α2a may achieve a sustained virological response off-treatment and HBsAg seroconversion. PegIFN-α2a will most likely remain the backbone of HCV treatment for the next few years, despite the availability of direct-acting antivirals that are expected to improve cure rates. However, many efforts are concentrated on developing new compounds, with the goal of administrating all oral regimens and eliminating PegIFN from anti-HCV treatment.